Meningkatkan Hasil Belajar Siswa SD melalui Model Teams Games Tournament dan Media Scrapbook - Esa Panji Satria; Irfai Fathurohman; Sekar Dwi Ardianti (Universitas Pendidikan Indonesia Kampus Serang, 2020)
Learning outcomes indicate the students' success in learning. When the learning result was good, the the learning means successful. In vice versa, when the learning means unsuccessful when the outcomes were poor. The problem of poor learning outcomes was found in fourth grade of State Elementary School 2 of Tenggeles. The poor learning outcomes were caused by unsuitable learning models and media applied. This study aimed to improve students’ learning outcomes by applying the Teams Games Tournament model and Scrapbook media. This research was a classroom action research with the subject of 19 students. The instrument of data collecting methods used tests and non tests in form of observation, documentation and interviews. The data was analysed quantitatively and qualitatively. Cognitif learning outcomes in Science subject improved from the first cycle I with an average of 69 with a classical completeness percentage by 47%, to be an average of 79 with classical completeness precentage of 84% at the cycle II. While the Indonesian language content improved from an average of 72 with a classical completeness percentage of 67% to be an average of 81 with classical completeness of 84%. The improvement of skill aspects obtained an average score of 71 in the first cycle I to be 83 in the cycle II. The result indicated that the use of TGT with Scropbook media can improve the students’ learning outcome in cognitive and skill aspects in elementary school level.